Anticipating binding constraints: An analysis of debt covenants - Teoh, Ken (Journal of Financial Intermediation, 2025)
This paper shows that anticipation can meaningfully impact inferences about the effects of covenant violations. Using textual analysis of SEC filings and earnings call transcripts, I construct a measure of covenant concerns that identifies instances where firms disclose forward-looking risks related to their debt covenants. On average, nearly 30 percent of U.S. non-financial firms report covenant concerns each year. While the real effects of covenant violations are robust for most outcomes, the estimated impact of some variables, including cash acquisitions, default risk, and credit line availability, can be overstated. This finding highlights the importance of selection around violation: firms that anticipate and successfully avoid violations differ systematically from firms that fail to avoid them.